Comparison of Short and Long-Term Results after Injection Laryngoplasty with Radiesse® Voice and Thyroplasty Type I in Unilateral Vocal Fold Palsy - Smatanová, Katarína; Burián, András; Dršata, Jakub; Krtičková, Jana; Kőnig-Péter, Anikó; Mejzlík, Jan; Chrobok, Viktor (Acta medica (Hradec Kralove), 2023)
OBJECTIVES: Unilateral vocal fold palsy independently of etiology results in glottic insufficiency leading to unfavorable short or long-term impact on voice quality. Our aim was to evaluate the effect of injection laryngoplasty using Radiesse® Voice and thyroplasty type I on glottic closure, voice quality and aerodynamics by comparing preoperative, short- and long-term results. MATERIALS AND METHODS: Data of 32 consent patients were reviewed between 2012 and 2023. All patients underwent either injection laryngoplasty (14 patients) or thyroplasty type I (18 patients) under local anesthesia. Maximum phonation time, glottic closure based on videolaryngostroboscopy, VHI-30 values and GRBAS scale were recorded prior, short-term (3 month) and long-term (12 months) after procedures for statistical comparison. Friedman test, Mann-Whitney test and Wilcoxon signed rank tests were used for statistical analysis. RESULTS: In injection laryngoplasty group, we found significant improvement in maximum phonation time (p = 0.002), grade of hoarseness (p = 0.002) and breathiness (p = 0.000) when comparing results before and short-term after procedure. In thyroplasty type I group we saw significant improvement of maximum phonation time (p = 0.000), glottic insufficiency (p = 0.000), all three VHI-30 components (p = 0.000), as well as grade of hoarseness, breathiness (both p = 0.000) and roughness (p = 0.011) of GRBAS scale when comparing voice outcome before and short-term after procedure. There was no significant difference in voice outcome results neither between short and long-term results nor between the two groups in any parameter. CONCLUSION: These results demonstrate both short and long-term efficiency of injection laryngoplasty and thyroplasty type I in the improvement of voice quality and glottic closure.
Keywords: Hoarseness; Humans; glottis; thyroplasty type I; unilateral vocal fold palsy; Vocal Cord Paralysis; výsledek terapie; Glottis; lidé; Laryngoplasty; chrapot; glottic closure; voice quality; Retrospective Studies; Treatment Outcome; retrospektivní studie; injection laryngoplasty; ochrnutí hlasivek; laryngoplastika